Non-contrast-enhanced 3.0T Whole-heart Coronary MRA: Comparison of Diagnostic Performance between mDixon and WHCA TFE Sequence Using SPIR in CAD Using Coronary Angiography as Reference - Huaying WANG; Yang CHEN; Peng HUANG; Yue LI; Gang ZHANG; Zhongsheng ZHANG; Haixia JI; Hao GUO; Heng MA (CT Lilun yu yingyong yanjiu)
Objective: To compare the diagnostic performance between mDixon sequence and WHCA TFE sequence using SPIR for non-contrast-enhanced coronary MRA in patients with suspected coronary artery disease (CAD). Method: This prospective study recruited 45 patients who were scheduled for X-ray coronary angiography (CAG) with suspected CAD in Yantai Yuhuangding hospital. Patients underwent both 3.0T WHCA TFE using SPIR and mDixon coronary MRA examinations before undergoing CAG. Two radiologists independently assessed coronary arteries in terms of subjective image quality (on a scale of 1~5, with 5 denoting the highest image quality), vessel length, vessel diameter, and presence of significant stenoses. CAG was used as the reference standard for detecting the presence of stenoses. Vessel length and diameter were compared between sequences using paired t-tests. Subjective image quality scores were compared between sequences using Wilcoxon tests. Sensitivity, specificity, and accuracy were compared between sequences using McNemar tests. Positive and negative predictive values were compared between sequences using the joint hypotheses test. Results: Two CMRA examinations were successfully performed in 40 (88.9%) of 45 patients for analysis. The objective image quality of 3.0T mDixon assessed by both radiologists was (3.9±0.9), and the 3.0T WHCA TFE using SPIR was (3.7±0.9). The mDixon sequence exhibited higher sensitivity, specificity, accuracy, positive predictive value, and negative predictive value in per-segment analysis (78.5% vs. 66.1%, 96.5% vs. 93.8%, 91.7% vs. 86.6%, 88.6% vs. 78.9%, and 93.4% vs. 88.7%) and higher sensitivity and accuracy in per-vessel analysis (89.4% vs. 81.6% and 89.1% vs. 83.3%). Conclusion: In comparison with 3.0T WHCA TFE sequence using SPIR, mDixon demonstrated superior diagnostic performance.